Influence of sex and disease etiology on the development of papilledema and optic nerve sheath extension in the setting of intracranial pressure elevation in children - Susanne Regina Kerscher; Jonas Tellermann; Julian Zipfel; Andrea Bevot; Karin Haas-Lude; Martin Ulrich Schuhmann (Brain and Spine)
Introduction: Dilatation of the optic nerve sheath diameter and swelling of the optic disc are known phenomena associated with intracranial pressure elevation. Research question: Do sex and disease etiology have an impact on the development of optic disc elevation and optic nerve sheath extension in children in the setting of ICP elevation? Fundoscopic papilledema and point-of-care-ultrasound techniques-optic nerve sheath diameter (US-ONSD) and optic disc elevation (US-ODE) - were compared in this regard. Material and methods: 72 children were included in this prospective study; 50 with proven pathology (e.g. pseudotumor cerebri, tumor), 22 with pathology excluded. Bilateral US-ONSD and US-ODE were quantified by US using a 12-MHz-linear-array-transducer. This was compared with fundoscopic optic disc findings and in 28 patients with invasive ICP values, stratified for sex and etiology. Results: In patients with proven disease, significant more girls (69%) had fundoscopic papilledema compared with boys (37%, p < 0.05). Girls had also larger US-ODE values (0.86 ± 0.36 mm vs. 0.65 ± 0.40 mm in boys). 80% of tumor patients had initial papilledema (100% girls, 79% boys), compared with 50% in pseudotumor cerebri (PTC) (83% girls, 30% boys). US-ONSD had no sex- and no etiology-specificity. Discussion and conclusion: Presence of papilledema appears to be influenced by sex and etiology, whereas US-ONSD is not. Girls seem more likely to develop papilledema under similar conditions. Male sex and PTC appear as risk factors for being undetected by fundoscopic findings. US-ONSD and US-ODE seem useful tools to identify pathologies with potentially increased ICP requiring treatment in children regardless of sex and etiology.